Peran Organizational Citizenship Behaviour (OCB) Dalam Memediasi Pengaruh Motivasi Intrinsik dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT.Cinemaxx Branch Lippo Plaza Yogyakarta - Maryati, Tri; Fernado, Aulia (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2018)
Intrinsic motivation is a drive that is not triggered from the outside but grows and develops from within a person. While Job Satisfaction is a condition where an employee feels satisfied with his job. Both of these things are able to encourage employee behavior to work beyond that set by the company and has nothing to do with the reward system. In this thesis, the author examines the influence of Intrinsic Motivation and Job Satisfaction on Employee Performance mediated by Organization Citizenship Behavior (OCB).Subjects in this study were employees of PT.Cinemaxx branch of Lippo Plaza Yogyakarta. Then the number of samples used are 55 respondents or all employees of the company, this number has been fulfilled from Cohen approach in determining the number of samples that is at least 45 respondents. The analysis technique used in this research is SEM (Structural Equation Modeling) using SmartPLS v.3 software.Based on the results of the analysis, Intrinsic Motivation has a positive and significant impact on Employee Performance and OCB, Job Satisfaction has positive and significant influence to Employee Performance and OCB, OCB has a significant and positive influence on Employee Performance, and OCB has positively and significantly between Intrinsic Motivation on Employee Performance, while OCB has no influence of mediation between Job Satisfaction on Employee Performance.